Positive episodic future thinking and its impact on the perceived performance anxiety in performing artists - Benedikt Gers; Klara Estela Weber; Mareike Altgassen (Frontiers in Psychology)
Performance anxiety is characterized by specific fears of social situations involving potentially being judged or scrutinized by others. Research on coping strategies has focused on breathing techniques, biofeedback training and the use of beta-blockers; less is known about the impact of positive episodic future thinking (i.e., the imagination of successful events in one’s personal future). Given previous evidence of beneficial effects of episodic future thinking on emotional well-being, we hypothesized that positive episodic future thinking may lead to a decrease of performance anxiety in performing artists. Fifty-four performing artists (27 higher and 27 lower performance anxious) filled in a Performance Anxiety Questionnaire and imagined three different performance related events (two envisioned situations focussed on the moments shortly before having to perform, interjected by the imagination of currently successfully performing on stage). Overall, the ‘higher performance anxious’ group showed higher perceived nervousness in all three envisioned events than the ‘lower performance anxious’ group [F(1,52) = 13.04, p < 0.001, η2 = 0.20]. Both groups showed a significant decrease in perceived nervousness during (p < 0.001) and after (p < 0.001) engaging in positive episodic future thinking, suggesting the intervention has similar anxiety-reducing effects on severely and less severely affected performing artists. Implications regarding positive episodic future thinking as a possible treatment for anxiety are discussed.